PELATIHAN BATIK ECOPRINT UNTUK MENINGKATKAN JIWA WIRAUSAHA SERTA DAPAT DIJADIKAN KHAS BATIK ECOPRINT JAMBI DENGAN JERNANG DESA NYOGAN KABUPATEN MUARO JAMBI - Maryani, Anis Tatik; Asra, Revi; Sarman, Sarman; Budiyati Ichwan, Budiyati; Eliyanti, Eliyanti (LPPM Universitas Islam 45 Bekasi, 2025)
Ecoprint is a fabric colouring technique that is done through direct contact by printing. The ecoprint technique is done by utilising plant parts. Nyogan Village, Jambi is a green area with many fallen leaves that are not utilised. The fallen leaves only become garbage that is wasted by burning. The implementation of community service activities is carried out with a participatory approach, so that the target audience can play an active role in every activity and problem solving. The delivery method is through an andragogy approach so that it is expected that there will be incentive-based interaction between the participants and the implementation team. The initial steps of the activity through preparation include determining the extension schedule and extension location in Nyogan Village. The implementation of the activity began with the socialisation of the introduction of ecoprint batik with jernang resin to PKK mothers and the community in Nyogan Village, providing questions and answers about ecoprint batik, the socialisation provided included an explanation of the technique of making ecoprint batik with jernang resin and the preparation of tools and materials in making ecoprint batik. The results of the service show that the service participants, namely PKK mothers, are motivated to create new batik creations so that they become community members who care about the environment by utilising plant materials from the yard productively through the ecoprint batik business.